La idoneidad de los profesores de religión católica y su desarrollo jurisprudencial en España - Otaduy Guerín, Jorge (Estudios eclesiásticos, 2013)
The Concordat between the Holy See and Spain sets out a framework for the teaching of the Catholic religion at non-university levels in the education system, which is compulsory for educational institutions and voluntary in terms of student attendance. Under the terms of the Concordat, the «nomination» of religion teachers to the relevant administrative authority is a right reserved to the ordinary of the diocese, so as to ensure the suitability of candidates for the post of religion teacher. The ordinary’s authority to revoke any such statement of suitability, and the State’s jurisdictional prerogative in overseeing such decisions, are matters of some dispute. A series of judgments handed down by the Spanish Constitutional Court since 2007 have addressed these issues. The European Court of Human Rights has also done so, in a 2012 judgment relating to Spain. This paper provides a comprehensive account of the question.